Adaptations of potato production to future climate change by optimizing planting date, irrigation and fertilizer in the Agro-Pastoral Ecotone of China - Jianzhao Tang; Huizi Bai; Shenghai Zhang; Dengpan Xiao; Zheng Tianzhu; De Li Liu; Bin Wang; Puyu Feng (Climate Risk Management, 2024)
Future climate change, especially rising temperature and varying precipitation will have significant impacts on potato production. Revealing the optimum planting date, irrigation schedule and fertilizer amount under future climate scenarios is critical for promoting sustainable potato production in the Agro-Pastoral Ecotone (APE). In this study, two representative stations of Wuchuan (WC) and Zhangbei (ZB) in APE were selected, firstly, we used well validated APSIM-Potato model to optimize the planting date of potato in future climate scenarios. Then the impacts of different combination of N fertilizer and irrigation on potato yield, N loss, water use efficiency (WUE), nitrogen use efficiency (NUE) and economic income were analyzed under optimal planting date. The future climate projection was provided by 13 Global Climate Models (GCMs) from the Coupled Model Inter-comparison Project phase 6 (CMIP6) under two emission scenarios of future societal development pathway (SSP) 245 and SSP585. Compared with baseline period (1981–2010), the planting windows during 2040 s (2031–2060) and 2080 s (2071–2100) were wider, and the optimal planting dates (OPDs) for rainfed potato should be arranged later under SSP245, but it should be earlier under SSP585. However, the OPDs for irrigated potato should advance under SSP245 and SSP585. Then, we analyzed the coupling effects of irrigation and nitrogen fertilizer on potato production under OPDs in future climate scenarios. Irrigation was carried out based on the soil water deficit within 1 m depth (IR, ranged from 10 mm (IR10) to 100 mm (IR1) with the interval of 10 mm) and fertilizer was set with 8 treatments (N, ranged from 0 kg ha−1 (N0) to 210 kg ha−1 (N7) with the interval of 30 kg ha−1). To achieve highest yield, maximum amount of N (N7, 210 kg ha−1) coupled with IR10 (irrigation applied if soil water deficit beyond 10 mm) should be applied for both WC and ZB station. However, these combinations would accumulatively decrease groundwater table (GDT) by 70.8–76.5 m (39.1–44.8 m) and 78.7–80.2 m (38.6–47.4 m) during 2040 s and 2080 s, and induce annual N loss by 21.6–27.3 kg ha−1 (24.7–25.3 kg ha−1) and 17.7–21.9 kg ha−1 (18.3–21.2 kg ha−1) at WC (ZB), respectively. Net income of potato under different combinations of irrigation and N fertilizer ranged from −10700 to 25,500 Yuan ha−1 and from −4100 to 26,600 Yuan ha−1 at Wuchuan and Zhangbei. To maximize the income of farmers, N4 (120 kg ha−1) coupled with IR9 (irrigation applied if soil water deficit beyond 20 mm) should be applied at the two study sites. Our results would be helpful in developing adaptable strategies for potato production to cope with future climate change in the APE.